Interpolation between W Dopant and Co Vacancy in CoOOH for Enhanced Oxygen Evolution Catalysis. Issue 2 (18th November 2021) - Dou, Yuhai; Yuan, Ding; Yu, Linping; Zhang, Weiping; Zhang, Lei; Fan, Kaicai; Al‐Mamun, Mohammad; Liu, Porun; He, Chun‐Ting; Zhao, Huijun
Abstract: Electronic structure engineering via integrating two defect structures with opposite modulation effects holds the key to fully unlocking the power of a catalyst. Herein, an interpolation principle is proposed to activate CoOOH via W doping and Co vacancies for the oxygen evolution reaction. Density functional theory suggests opposite roles for the W dopant and the Co vacancy but a synergy between them in tuning the electronic states of the Co site, leading to near‐ideal intermediate energetics and dramatically lowered catalytic overpotential. Experimental studies confirm the modulation of the electronic structure and validate the greatly enhanced catalytic activity with a small overpotential of 298.5 mV to drive 50 mA cm −2 . The discovery of the interpolation between dopants and vacancies opens up a new methodology to design efficient catalysts for various electrochemical reactions. Abstract : An interpolation principle between W dopant and Co vacancy with opposite modulation effect is proposed to tune the electronic structure of CoOOH for enhanced oxygen evolution reaction. As a result, near‐optimal electronic states and near‐ideal intermediate energetics are achieved, leading to high catalytic activity. Such an interpolation principle can open up a new methodology for efficient catalyst design.